Compressive deformation behavior and microstructure evolution of AM80 magnesium alloy under quasi-static and dynamic loading. (November 2017) - Guo, Pengcheng; Li, Luoxing; Liu, Xiao; Ye, Tuo; Cao, Shufen; Xu, Congchang; Li, Shikang
Highlights: As-received AM80 magnesium in solution-treated state is impacted under quasi-static and dynamic loading conditions with strain rates ranging from 3 × 10 −5 to 2300 s −1 . The studied alloy illustrates a negative strain rate sensitivity (SRS) under quasi-static loading while a positive SRS under dynamic loading. In addition, the flow stress slightly increases as the strain rate is increased from 1400 to 2300 s −1 . The microstructure evolution during impact deformation resulted in different flow stress behaviors has been discussed in detail. Abstract: To investigate the stress response and the corresponding microstructure evolution of AM80 magnesium alloy under quasi-static and dynamic loading, as-cast AM80 alloy was compressed over a wide range of strain rate at room temperature. The experimental results show that the flow stress responses exhibit a negative strain rate sensitivity (SRS) under quasi-static loading while a positive SRS under dynamic loading. Furthermore, deformation bands generated under dynamic loading are relatively homogeneous with a visibly higher density compared with those generated under quasi-static loading. The activation of extension twinning is significantly enhanced under dynamic loading. The dislocation density and extension twins apparently decrease as the applied strain rate increases from 1400 to 2300 s −1 due to the adiabatic temperature rise, which results in the limited increase in flow stress.